LEGALITAS SURAT KETERANGAN TANAH YANG DIKELUARKAN OLEH KEPALA DESA SEBAGAI DASAR TRANSAKSI JUAL BELI TANAH (Studi Kasus Putusan Mahkamah Agung No. 31.PK/TUN/2005) - TRI HANDAYANI (PREMISE LAW JURNAL, 2016)
Land plays an important position for the Indonesian people in general and for farmers in the rural area in particular because it constitutes their main source of life and earnings. The research used judicial normative and descriptive analytic method. The result of the research showed that land transact based on land certificate issued by a village head was valid and has legal force. However, after the land transact based on the land certificate issued by the village head, the buyer has to register the land in the Land Office where it is located. Keywords: Land Certificate, Village Head, Land Transact